An automated model based approach to mobile UI specification and development - Ribeiro, António Nestor (2016)
One of the problems of current software development lies on the existence of solutions to address properly the code portability for the increasing number of platforms. To build abstract models is one efficient and correct way to achieve this. The Model-Driven Software Engineering (MDSE) is a development methodology where models are the key for all project lifecycle, from requisites gathering, through modelling and to the development stage, as well as on testing. Pervasive computing demands the use of several technical specifications, such as wireless connections, advanced electronics, and the Internet, as well as it stresses the need to adjust the user interface layer to each one of the platforms. Using a model-driven approach it is possible to reuse software solutions between different targets, since models are not affected by the device diversity and its evolution. This paper reports on a tool, which is highly parameterizable and driven to support Model-2-Model and Model-2-Code transformations. Also, instead of using a predefined technology, the tool was built to be scalable and extensible for many different targets and also by addressing the user interface layer generation.